HUBUNGAN STATUS GIZI (IMT) DAN AKTIVITAS FISIK DENGAN KUALITAS HIDUP LANSIA DI RW 02 JATIBENING BEKASI TAHUN 2020 - Danyaa Allya Salsabilla, DAS (2021)
Life expectancy of the world's population, including Indonesia, has increased significantly for the last 10 years. This has resulted in a rapid increase in the number of elderly people, if this is not balanced with a good quality of life it can cause health problems. This research was aims to analyze the relationship between nutritional status (BMI) and physical activity with the quality of life of the elderly in RW 02 Jatibening Village, Bekasi. This research method is analytic observational with a cross-sectional design. The respondent was selected by using simple random sampling technique with a total sample of 63 elderly (> 60 years). Data collection was carried out in December 2020 - January 2021. Nutritional status data obtained through direct measurement using a digital scale and a microtoise height meter. Physical activity and quality of life data were obtained through filling out a questionnaire with interviews using the Physical Activity Scale for the Elderly (PASE) and the World Health Organization Quality of Life Old (WHOQOL-OLD). Data processing using the Spearman rank correlation test. The results showed that there was a relationship between nutritional status and quality of life (r = 0.471; p = 0.000) and there was a relationship between physical activity and quality of life (r = 0.673; p = 0.000) in RW 02 Jatibening Village, Bekasi. Based on the test results above, it can be concluded that nutritional status and physical activity have an influence on the quality of life of the elderly